2000
DOI: 10.1051/analusis:2000280445
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of spin-trapping EPR techniques for the measurement of NO production in biological systems

Abstract: In this overview of NO spin-trapping methods, we have pointed out their main advantages over frozen solution EPR spectroscopy detection of nitrosylated metalloproteins: improved sensitivity, potential specificity and time-resolution. A few simple ideas concerning EPR methodology have been recalled. Examples of possible artefacts, sometimes unexpected, which can easily be encountered in any analytical methods have been described. New methodological developments have also been mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 112 publications
0
13
0
1
Order By: Relevance
“…32 It is believed that free radicals are directly implicated in the pathogenesis of diabetes and that levels of •NO radicals in type 2 diabetes patients are increased. [33][34][35] A number of studies have demonstrated lower levels of nitrite/nitrate plasma in diabetic patients compared to the healthy controls. 36,37 Diabetic patients often experience elevated glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…32 It is believed that free radicals are directly implicated in the pathogenesis of diabetes and that levels of •NO radicals in type 2 diabetes patients are increased. [33][34][35] A number of studies have demonstrated lower levels of nitrite/nitrate plasma in diabetic patients compared to the healthy controls. 36,37 Diabetic patients often experience elevated glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Also, to obtain coherent calibration results, one must work under very strict conditions of time, pH and temperature because even small changes in these parameters can greatly influence the hemoglobin reaction. EPR spectroscopy is also widely used for NO detection through the development of several methods of NO-trapping [17], but its heaviness and poor detection limit (1 mM) make it unsuitable for routine uses. Finally, gas phase chemiluminescence assay [18], based on the chemiluminescent properties of excited NO Ã 2 formed from NO that reacts with ozone, offers real utility and ease for some specific applications, especially for NO exhaled gas.…”
Section: Introductionmentioning
confidence: 99%
“…Дальн ейший прогресс в области использования стабильных парамагнетиков для решения разнообразных биологических задач нашел отражени е в мног очисленных обзорных статьях и монографиях, нап риме р [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Для динами ческ ой биохимии несомненный и нтерес представляют локальные конформац ионные и зменения белк овых молекул в растворах.…”
Section: решение других биологических проблем с помощь ю стабильных рunclassified